Bringing function to the forefront of cell therapy: how do we demonstrate potency? - Lowdell, Mark W.; Weil, Ben (Frontiers in Immunology, 2023)
Unlike conventional pharmaceuticals, biologics and Advanced Therapy Medicinal Products (ATMPs) are required to meet a standard of "potency" as part of the final release criteria at completion of manufacture. During early phase clinical trials, most regulatory agencies have been willing to accept very immature potency assays with an expectation that these will be improved, qualified and validated during the clinical development of the drug to Marketing Authorisation Application (MAA) or Biologics License Application (BLA) submission.This model of continuous development of potency assay in parallel with drug development has already led to at least two notable problem cases; namely Iovance and Mesoblast. Both companies completed successful phase III clinical trials but, in both cases, the initial BLA was rejected on the basis that their potency assay for drug product release was inadequate. Fortunately these issues appear to have been overcome in March of this year, with Mesoblast receiving acceptance of their BLA for Remestemcel and Iovance obtaining a rolling BLA approval for Lifileucel.